Evaluasi Kebijakan Sekolah Inklusi Berbasis Permendiknas No 70 Tahun 2009: Tantangan dan Rekomendasi Strategis: Evaluation of Inclusive School Policy Based on Regulation of the Minister of National Education No. 70 of 2009: Challenges and Strategic Recommendations - Delis Rahayu Suciani; Lisda Citra Dewi; Radin Radin; Leli Halimah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Regulation of the Minister of National Education No. 70 of 2009 serves as the legal foundation for inclusive education in Indonesia, mandating that every regency and city provide inclusive schools at all educational levels. However, more than a decade after its enactment, a significant gap persists between policy and actual practice. This study aims to evaluate the implementation of inclusive education policy in primary schools and identify the systemic barriers hindering its execution. A mixed-methods approach was employed, utilising in-depth interviews, participatory observation, and document analysis across 12 inclusive primary schools in three provinces. The findings reveal four major challenges: limited teacher competence in handling students with special needs, a shortage of certified Special Support Teachers (GPK), school facilities that are not yet disability-friendly, and weak coordination among central and regional governments and educational institutions. Based on these findings, the study recommends three strategies: strengthening competency-based training for inclusive education teachers, revising budget allocation mechanisms for inclusive schools, and establishing an integrated, data-driven monitoring system. Although Regulation No. 70 of 2009 paved the way for inclusive education in Indonesia, the divide between regulation and practice remains wide. Teachers lack sufficient inclusive education competencies, certified support teachers are scarce, school facilities do not accommodate students with disabilities, and inter-governmental coordination remains fragmented. The three resulting recommendations are intended to serve as a guide for policymakers in strengthening an inclusive education ecosystem that is equitable and sustainable. True inclusive education is not merely a matter of written regulations but a shared commitment that must be realised even in the most remote classrooms.